Single K+ currents during differentiation of embryonic muscle cells in vitro - Zemková, H; Vyskocil, F; Tolar, M; Vlachová, V; Ujec, E (Biochimica et biophysica acta, 1989)
After 3-7 days in culture, chicken myotubes possess five types of K+ channel: two high-conductance channels of 195 and 105 pS which are sensitive to tetraethylammonium (TEA), an ATP-sensitive channel of 64 pS and two low-conductance channels of 40 and 15 pS which are insensitive to TEA and ATP. The same population of channels is to be found in EGTA-treated muscle cells with blocked fusion and, with the exception of the ATP-sensitive channel, also in 1-day-old myoblasts. There are differences between myoblasts and myotubes in the percentage of incidence of individual channel types. High-conductance K+ channels are most frequently to be observed in myotubes, but they are rare in myoblasts and EGTA-treated cells where low-conductance K+ channels predominate.
Keywords: adenosintrifosfát; Muscles; tetraethylamonium; Animals; tetraethylamoniové sloučeniny; Electric Conductivity; kultivované buňky; Adenosine Triphosphate; buněčná membrána; Tetraethylammonium; membránové potenciály; kuřecí embryo; Chick Embryo; Egtazic Acid; elektrická vodivost; Electrophysiology; Cells, Cultured; elektrofyziologie; EGTA; zvířata; draslíkové kanály; Membrane Potentials; svaly; Cell Membrane; Tetraethylammonium Compounds; Potassium Channels